A Deep Learning Approach for Recognizing the Noon Rule for Reciting Holy Quran - Osman, Hanaa Mohammed; Mustafa, Ban Sharief; Mahmood, Basim Mohammed (Program Studi Teknik Elektro Universitas Khairun, 2024)
Ahkam Al-Tajweed represents the most precious religious heritage that is in critical need to be preserved and kept for the next generation. This study tackles the challenge of learning Ahkam Al-Tajweed by developing a model that considers one of the rules experienced by early learners in the Holy Quran. The proposed model focuses, specifically, on the